1992
DOI: 10.1083/jcb.117.2.449
|View full text |Cite
|
Sign up to set email alerts
|

A synthetic peptide derived from the carboxy terminus of the laminin A chain represents a binding site for the alpha 3 beta 1 integrin

Abstract: Abstract. The purpose of this study was to identify the binding site(s) within laminin for the a3ß, integrin receptor. It has been previously shown, using proteolytic fragments and anti-laminin antibodies, that the region in laminin for a3ß, integrin binding is localized to the carboxy-terminal region at the end of the long arm

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
69
0

Year Published

1995
1995
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(70 citation statements)
references
References 49 publications
(106 reference statements)
1
69
0
Order By: Relevance
“…The ®bulin-1 binding site with Engelbreth-HolmSwarm tumor laminin has been mapped to a site contained within the E3 fragment (Pan et al, 1993b;Brown et al, 1994), a fragment derived from the carboxy terminus of the a chain. This domain has been shown to mediate integrin a3b1 binding (Gehlsen et al, 1989(Gehlsen et al, , 1992 and lies in the vicinity of binding sites for the integrins a6b1 (Aumailley et al, 1990;Hall et al, 1990;Sonnenberg et al, 1991) and a7b1 (Kramer et al, 1991;von der Mark et al, 1991). In addition, the laminin receptor dystroglycan binds to the E3 fragment (Gee et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…The ®bulin-1 binding site with Engelbreth-HolmSwarm tumor laminin has been mapped to a site contained within the E3 fragment (Pan et al, 1993b;Brown et al, 1994), a fragment derived from the carboxy terminus of the a chain. This domain has been shown to mediate integrin a3b1 binding (Gehlsen et al, 1989(Gehlsen et al, , 1992 and lies in the vicinity of binding sites for the integrins a6b1 (Aumailley et al, 1990;Hall et al, 1990;Sonnenberg et al, 1991) and a7b1 (Kramer et al, 1991;von der Mark et al, 1991). In addition, the laminin receptor dystroglycan binds to the E3 fragment (Gee et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Purification of ␣3␤1 Integrin-The purification of ␣3␤1 integrin was performed as described previously (33). Briefly, cells in confluent were detached with TBS(ϩ) (20 mM TrisHCl, pH 7.5, 130 mM NaCl, 1 mM CaCl 2 , and 1 mM MgCl 2 ) and washed with TBS(ϩ).…”
Section: Methodsmentioning
confidence: 99%
“…Among the integrins, α1β1 (Hall et al, 1990), α2β1 (Elices and Hemler, 1989;Languino et al, 1989;Lotz et al, 1990), α3β1 (Gehlsen et al, 1992), α6β1 (Sonnenberg et al, 1988;Lotz et al, 1990) and α6β4 (Lotz et al, 1990;Lee et al, 1992) integrins have been reported to mediate binding to LM in static condition. To determine which integrins function in flow condition, we examined the adhesion behaviour of Colo201 pretreated with functionally blocking mAbs to these integrins.…”
Section: Tethering and Spreading On Lm Is Partially Mediated By α6β1 mentioning
confidence: 99%